1999
DOI: 10.1080/08035259950168586
|View full text |Cite
|
Sign up to set email alerts
|

Prone position in spontaneously breathing infants with pneumonia

Abstract: This study was designed to evaluate further the effect of prone positioning on oxygen saturation (SpO2) and respiratory mechanics in spontaneously breathing infants with pneumonia. SpO2 and respiratory mechanics were measured in the supine and prone positions in 17 infants. Prone positioning resulted in statistically significant increases in mean (+/- SD) SpO2 (95.52+/-2.87 to 98.00+/-2.40%, p = 0.0002) and respiratory system compliance (5.99+/-2.52 to 7.93+/-4.30 ml/cm H2O, p = 0.02). This suggests that prone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…38 In a small case-control study with 40 neonates with radiologically confirmed moderate pneumonia in Beijing, China, Li et al 60 found that unswaddled infants in the prone position had 18% higher oxygen tension than swaddled supine infants and 12% higher oxygen tension than unswaddled supine infants. The fact that the oxygen saturation level is higher in the prone than in the supine position is supported by a small case-control study by Chaisupamongkollarp et al 61 in which prone positioning in spontaneously breathing infants with pneumonia resulted in a statistically significant increase in mean oxygen saturation. Kahn et al 33 also found indications for cardiorespiratory compromise associated with swaddling, especially tight swaddling.…”
Section: Respiratory Infectionsmentioning
confidence: 51%
“…38 In a small case-control study with 40 neonates with radiologically confirmed moderate pneumonia in Beijing, China, Li et al 60 found that unswaddled infants in the prone position had 18% higher oxygen tension than swaddled supine infants and 12% higher oxygen tension than unswaddled supine infants. The fact that the oxygen saturation level is higher in the prone than in the supine position is supported by a small case-control study by Chaisupamongkollarp et al 61 in which prone positioning in spontaneously breathing infants with pneumonia resulted in a statistically significant increase in mean oxygen saturation. Kahn et al 33 also found indications for cardiorespiratory compromise associated with swaddling, especially tight swaddling.…”
Section: Respiratory Infectionsmentioning
confidence: 51%
“…The flow rate should be regulated to keep the bag of the mask inflated during inspiration and expiration. Using the prone position for infants may improve hypoxia and the respiratory system compliance 62 and should be attempted if hypoxia is difficult to treat. Oxygen should be discontinued when the child is improving clinically and the transcutanous saturation is above 90% in room air.…”
Section: Methods Of Oxygen Administrationmentioning
confidence: 99%
“…The prone position is most often applied to mechanically ventilated patients. Three cases of its use in spontaneously breathing patients, in addition to cases of infant pneumonia, have been described (3–5).…”
mentioning
confidence: 99%